Analisis Gastronomi Makanan Tradisional Melayu Mie Lendir sebagai Daya Tarik Wisata Batam - Miratia Afriani; Rosie Oktavia Puspita Rini; Agung Arif Gunawan (STIEPAR YAPARI Bandung, 2022)
This study analyzes the potential of gastronomy tourism in tourism development in Batam. The concept of culinary tourism at this time has developed and experienced a shift in the understanding of culinary tourism itself. At this time the tourists come to an area not only limited to them focusing on the food alone. Tourists want to get additional value or experience when they come to visit an area/region. Either they know historyand, culture or they can participate in the process of making it. called gastronomy tourism. Mie Lendir is a type of food that has undergone culturalization of Malay and Chinese culture. By bringing up the gastronomy of Mie Lendir, it is hoped that tourists can feel the different and uniqueness of the product and, they can also feel the value and understand the process of cultivating Mie Lendir culture. The type of research used is descriptive qualitative by providing an overview of the Gastronomic Tourism Potential of Mie Lendir as a Batam Tourist Attraction. The research method used is structured interviews directly with research sources. The survey method applied is a descriptive survey. The results of this study, Mie Lendir has the potential to be used as a gastronomic tour in Batam because it also has cultural, historical and educational values ??for the Malay community which has its own uniqueness.